Witkop tooth and nail syndrome: a case report - S. DEVADAS, B. VARMA, J. MUNGARA, T. JOSEPH, & T. R. SARASWATHI (Paediatric Dentistry, 2005)
The ectodermal dysplasias are a clinically and genetically heterogeneous group of more than 120 syndromes involving ectodermally derived structures [1].